Evaluation of formulated blending of fertilizers with increasing doses and addition of organic matter in dark tobacco in a sandy soil under greenhouse conditions - Cóndor G, Aníbal (2002)
This trial compares 3 formulated blending of fertilizers (a traditional blending, a mineral fertilizer 10-15-20 and an organic-mineral fertilizer 8-12-16) in increasing doses, with and without the addition of organic matter (worm compost) in tobacco cultivation. This trial was conducted in a sandy soil of irrigation using 2 dark tobacco seedlings per pot. Soil fertilization for each NPK doses in mg.kg-1 was: low dose (160-60-80), medium dose (320-120-160) and high dose (480-180-240). A complete randomized design with factorial arrangement and three replications was used. Replications were 4 kg soil pots. The evaluation consisted in measuring the yield of the fresh weight of the aerial part and the dry weight of the aerial and rooted part of the plants. It could be seen that none of the formulated blending used were much better among them in terms of the fresh and dry matter evaluated, with an average of 432,5 g and 112,6 g, respectively. In this way, there are three alternatives when fertilizing tobacco. However, when we use the organic-mineral fertilizer we can get more benefits for soils because there is a 25% of organic matter in its composition for each 100 kg of the fertilizer. While doses are increased yields also increase, the direct effect of fertilizers was evident in the sandy soil without a high visible salinity. Besides, it could be seen the poor fertility of the soil when comparing the additional treatment 0-0-0 with the other ones producing more than 300% in terms of yield. There is no significant effect in the interaction fertilizer-organic matter in the production of aerial fresh matter and total dry matter due to the low application of organic matter (1%).